A 450mpa grade galvanised dual phase steel and method of production thereof

CN117867380BActive Publication Date: 2026-10-20BENGANG STEEL PLATES CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311737223.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2026-10-20
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

该专利炼钢工序未明确具体工艺参数,不利于铸态组织与表面质量的稳定控制,即使在Ar3以上进行高温终轧但仍有较明显的带状组织倾向

Benefits of technology

[0022]1、本发明添加适量Cr元素来保证淬透性,未添加成本较高的Mo元素,Si元素含量较低可以获得良好的镀锌质量,添加适量细晶元素Ti,细化组织并提升整体性能水平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867380B_ABST
    Figure CN117867380B_ABST
Patent Text Reader

Abstract

The application discloses a 450MPa galvanized dual-phase steel and a production method thereof, a proper amount of Cr is added to ensure hardenability, Mo with a higher cost is not added, and a tensile strength meeting a standard requirement can be obtained; a dew point and oxygen content in a continuous annealing process are controlled to be low, a good coating quality can be obtained through a low-Si component design, a good slab surface quality and a hot-rolled plate quality; through component design, converter smelting and precise control of secondary refining, the nitrogen content and inclusion content in the steel are effectively reduced, the castability of the molten steel is improved, the pouring temperature, the pulling speed and the soft reduction amount are strictly controlled in a continuous casting pouring process, and good slab surface quality and internal quality are obtained; a proper amount of fine-grain element Ti is added, high cold-rolling reduction is combined with low-temperature coiling, and better organizational morphology and mechanical properties can be obtained after continuous annealing and galvanizing; the grain structure after the continuous annealing is fine, the yield strength can be effectively controlled through finishing, and the requirements of the yield strength ratio, the stamping performance and the flange flanging performance are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgical technology, specifically relating to a 450MPa grade galvanized duplex steel and its production method. Background Technology

[0002] Reducing vehicle weight and improving safety are design standards for automakers, crucial for meeting customer needs, legal regulations, and standards. The use of high-strength steel is considered an effective method for weight reduction. Meanwhile, the use of galvanized high-strength steel is increasing due to stricter corrosion protection requirements. Duplex steel, with its advantages of low yield strength, high initial work hardening rate, good plasticity, and high impact energy absorption, is widely used in the automotive industry.

[0003] In the prior art, patent application number CN201410133681.9 discloses "a cold-rolled hot-dip galvanized duplex steel and its preparation method," with the following chemical composition by weight percentage: C: 0.02-0.05%, Si: 0.1-0.2%, Mn: 0.8-1.3%, P≤0.01%, S≤0.01%, Al: 0.04-0.08%, Cr: 0.5-0.7%, V≤0.01%, B≤0.005%, and the balance being Fe. This patent has a high Si content, which reduces the surface quality of the steel plate. Furthermore, the hot rolling process lacks a clearly defined cooling path and hot-rolling reduction amount, which is detrimental to the stable control of the microstructure and surface quality of the hot-rolled coil. Patent application CN202110896057.4 discloses "450MPa grade hot-dip galvanized duplex steel and its production method," with the chemical composition by mass percentage as follows: C 0.03–0.10%, Si 0.20–0.60%, Mn 1.20–2.00%, P≤0.020%, S≤0.010%, Als 0.015–0.070%, N≤0.0060%, and the remaining elements being Fe and unavoidable impurities. The high Si content in this patent reduces the surface quality of the steel plate, and the three-stage heating method with different rates increases the difficulty of control, without clearly defining the different heating stages.

[0004] Patent application CN202111273813.4 discloses "a 450MPa grade hot-dip galvanized duplex steel with high work hardening rate and surface quality and its production method." Its chemical composition by weight percentage is: C 0.045%–0.06%, Si 0.1%–0.2%, Mn 1.25%–1.35%, Al 0.03%–0.06%, Cr 0.36%–0.41%, Mo 0.1%–0.14%, P≤0.015%, S≤0.006%, N≤0.004%, with the balance being Fe and unavoidable impurities. This patent adds the relatively expensive element Mo, increasing the alloy cost. Furthermore, the steelmaking process lacks clearly defined process parameters, which is detrimental to the stable control of the as-cast microstructure and surface quality. Patent application number CN201110077800.X discloses "a high-strength cold-rolled hot-dip galvanized duplex steel sheet and its manufacturing method," whose composition by mass percentage is C: 0.03%–0.15%, Si≤0.15%, Mn: 1.00%–1.75%, P≤0.015%, S≤0.012%, Al: 0.02%–0.15%, Cr: 0.35%–0.75%, Cu: 0.02%–0.15%, Ti 0.010–0.035%, N≤0.005%, and satisfies 1.5%≤Mn+1.29Cr+0.46Cu≤2.5%, with the balance being Fe and unavoidable impurities. This patent lacks specific process parameters for the steelmaking process, which is detrimental to the stable control of the as-cast microstructure and surface quality. Even with high-temperature final rolling above Ar3, a significant tendency towards banded microstructure still exists. Summary of the Invention

[0005] In order to overcome the defects of the existing technology, the present invention produces 450MPa grade galvanized duplex steel with good plating performance, formability and surface quality through chemical composition design and precise process control, which can meet the requirements of lightweighting for the use of internal structural components and complex structural components of the vehicle body.

[0006] To achieve the above-mentioned objective, this invention provides a 450MPa grade galvanized duplex steel, wherein the galvanized duplex steel, by weight percentage, comprises the following components: C: 0.04–0.08, Si: 0.020–0.060, Mn: 1.30–1.60, P≤0.020, S≤0.010, Al: 0.015–0.055, Cr: 0.30–0.50, Ti: 0.015–0.040, B: 0.0020–0.0040, with the remainder being Fe and unavoidable impurities.

[0007] In the composition design, an appropriate amount of Cr element is added to ensure hardenability, while the more expensive Mo element is not added. The low Si element content can achieve good zinc plating quality. An appropriate amount of fine-graining element Ti is added to refine the microstructure and improve the overall performance level.

[0008] A method for producing 450MPa grade galvanized duplex steel, the method comprising the following steps in sequence: hot metal pretreatment → converter smelting → ladle refining → continuous casting → slab heating → hot continuous rolling → laminar flow cooling → coiling → pickling → cold continuous rolling → continuous annealing and galvanizing → finishing.

[0009] The molten iron pretreatment includes desulfurizing the molten iron to S≤0.010%;

[0010] Converter smelting: First, scrap steel is added to the oxygen top and bottom blowing converter, using only high-quality scrap steel. Then, molten iron is added to the oxygen top and bottom blowing converter. The final concentration of C in the converter is controlled to be ≤0.04%, P ≤0.015%, and the tapping temperature is ≥1650℃. Before tapping, the ladle is pre-blown with argon for 1-2 minutes. Deoxidation and alloying begin when 1 / 5 of the steel has been tapped, and alloying is completed when 4 / 5 of the steel has been tapped. The amount of deoxidizer added is 1.5-2.0 kg / t, the amount of ferrosilicon alloy added is 2.2-2.4 kg / t, the amount of low-carbon ferromanganese added is 10-11 kg / t, the amount of ferrosilicon alloy added is 4-5 kg / t, and the amount of low-carbon ferrochrome added is 2-3 kg / t. The Al content in the ladle is controlled at 0.005-0.020%, and N ≤25 ppm.

[0011] Ladle refining: The molten steel is refined using a slightly positive pressure operation to reduce nitrogen absorption during the process; 800-1000 kg of quicklime is added in 2-3 batches; aluminum granules and calcium carbide are used to create reducing slag to ensure good slag fluidity; calcium treatment: 200-250 m of pure calcium wire is fed in the first furnace run, and 180-200 m of pure calcium wire is fed in the second furnace run, followed by argon blowing for 1-2 minutes after the calcium wire feeding is completed; soft blowing time is ≥10 minutes, including 5 minutes of intermediate blowing followed by soft blowing. Argon blowing is used to fully remove inclusions by allowing them to float to the surface. After argon blowing, the amount of covering agent added to the bulk pack is 80-120 kg / furnace. Alloying requirements: Si, Mn, B and Cr are controlled at the median value, C is controlled at 0.060-0.070%, and Al is controlled at 0.025-0.050%. The temperature of the furnace arriving at the station for the start-up furnace is 1580±10℃, and the temperature leaving the station is 1600±10℃. The temperature of the furnace arriving at the station for the continuous casting furnace is 1555±10℃, and the temperature leaving the station is 1575±10℃.

[0012] Continuous casting: Independent pouring is adopted, with protective pouring throughout. The argon flow rate between the tundish top nozzle and the submerged entry nozzle plate is 10-14 NL / min, the stopper rod argon flow rate is 8-10 NL / min, and the top nozzle argon flow rate is 14-16 NL / min. Before pouring, the tundish is purged with argon for 2-3 minutes, and a calcium addition line of 20-40m is added. During pouring, the ladle must be lowered to the bottom, and the protective sleeve insertion depth is ≥200mm. Low-carbon protective slag is used in the crystallizer, and low-carbon protective slag is used in the tundish. Carbon or carbon-free covering agent; tundish baking ≥2.5h, tundish and submerged entry nozzle inner wall baking temperature ≥1100℃, tundish temperature controlled 10~25℃ above liquidus temperature; soft reduction 2.2~2.6mm; constant casting speed maintained during steel casting process, target casting speed 1.25m / min, casting speed range 1.20~1.30m / min; start-up furnace arrival temperature 1595±10℃, continuous casting furnace arrival temperature 1570±10℃.

[0013] Slab heating: The slab is heated by a walking beam furnace with a preheating section of 950±20℃, a heating section of 1150±20℃, a soaking section of 1230±20℃, and a heating time of 2.5±0.5h.

[0014] Hot continuous rolling: the initial rolling temperature is 1130±20℃, the final rolling temperature is 870±20℃, the finishing mill inlet is descaled with high-pressure water of ≥20MPa, and the finishing mill stands are descaled with high-pressure water of ≥10MPa.

[0015] Laminar flow cooling: After exiting the finishing mill, the strip is cooled to 650-700℃ by laminar water cooling.

[0016] Winding: After laminar flow cooling, air cool for 10-20 seconds to the winding temperature of 550-600℃.

[0017] Pickling: The pickling temperature is 70-90℃, the pickling speed is 60-180m / min, the free HCl concentration in pickling tank #1 is ≥40g / l, and the free HCl concentration in pickling tank #3 is ≥140g / l.

[0018] Cold continuous rolling: cold rolling reduction rate ≥70%.

[0019] Continuous annealing and galvanizing: The preheating section heats the strip steel to 150–180℃ at a rate of 2–6℃ / s; the heating section heats the strip steel to 820–850℃ at a rate of 2–4℃ / s; the soaking section holds the strip steel at 820–850℃ for 50–110s; the slow cooling section cools the strip steel to 680–750℃ at a rate of 5–10℃ / s; the rapid cooling section cools the strip steel to 450–480℃ at a rate of 10–20℃ / s; the equalization section activates the edge insulation function to ensure that the transverse temperature difference of the strip steel is less than 5℃, improving the stability of the steel plate performance; the exit temperature of the equalization section is 450–470℃; the temperature of entering the zinc pot is 455–460℃, and the galvanizing time is 2–5s; the dew point inside the furnace is ≤-40℃, and the oxygen content is ≤2ppm.

[0020] Finishing: The finishing elongation rate is 0.4%–0.8%.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] 1. This invention adds an appropriate amount of Cr element to ensure hardenability, does not add the more expensive Mo element, and has a low Si element content to obtain good zinc plating quality. Adding an appropriate amount of fine-graining element Ti refines the microstructure and improves the overall performance level.

[0023] 2. This invention effectively reduces the nitrogen and inclusion content in steel and improves the castability of molten steel through chemical composition design and precise control of converter smelting and ladle refining. The continuous casting process strictly controls the casting temperature, casting speed and soft reduction to obtain good surface and internal quality of the billet.

[0024] 3. The hot-rolled steel plate of the present invention has good surface quality, and the microstructure of the hot-rolled plate is refined by low-temperature coiling, which is beneficial to obtaining better microstructure and mechanical properties after continuous annealing and galvanizing.

[0025] 4. The continuous annealing process of this invention has low dew point and oxygen content control. Good coating quality can be obtained through low Si composition design, good billet surface quality, and hot-rolled plate quality. Attached Figure Description

[0026] Figure 1 Micrograph of the 450MPa grade galvanized duplex steel prepared in Example 1;

[0027] Figure 2 Micrograph of the 450MPa grade galvanized duplex steel prepared in Example 2. Detailed Implementation

[0028] The present invention will be further described below with reference to specific embodiments, but this does not limit the invention in any way. To avoid redundancy, unless otherwise specified, the raw materials used in the following embodiments are all commercially available products, and the methods used are all conventional methods unless otherwise specified.

[0029] A 450MPa grade galvanized duplex steel, wherein the galvanized duplex steel is composed of the following components by weight percentage: C: 0.04-0.08, Si: 0.020-0.060, Mn: 1.30-1.60, P≤0.020, S≤0.010, Al: 0.015-0.055, Cr: 0.30-0.50, Ti: 0.015-0.040, B: 0.0020-0.0040, with the remainder being Fe and unavoidable impurities.

[0030] The finished steel plate prepared in the example was subjected to mechanical property testing. The testing standard was GB / T228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature". P6 specimens were used, and the specimen direction was longitudinal.

[0031] Example 1

[0032] A method for producing 450MPa grade galvanized duplex steel, the method comprising the following steps in sequence: hot metal pretreatment → converter smelting → ladle refining → continuous casting → slab heating → hot continuous rolling → laminar flow cooling → coiling → pickling → cold continuous rolling → continuous annealing and galvanizing → finishing.

[0033] S1. Hot metal pretreatment: The sulfur content of the hot metal after desulfurization is 0.008%.

[0034] S2. Converter smelting: First, 10% of the refined scrap steel by mass is added to the oxygen top and bottom blowing converter, and then 90% of the molten iron by mass is added to the oxygen top and bottom blowing converter. The final carbon content of the converter is 0.033%, the phosphorus content is 0.012%, and the tapping temperature is 1660℃. Before tapping, the ladle is pre-blown with argon for 2 minutes. Deoxidation and alloying begin when 1 / 5 of the steel has been tapped, and alloying is completed when 4 / 5 of the steel has been tapped. The amount of deoxidizer added is 1.80 kg / t, the amount of ferrosilicon alloy added is 2.24 kg / t, the amount of low-carbon ferromanganese added is 10.45 kg / t, the amount of ferrosilicon alloy added is 4.26 kg / t, and the amount of low-carbon ferrochrome added is 2.21 kg / t. The ladle contains 0.015% Al and 18 ppm N.

[0035] S3. Ladle Refining: The molten steel is refined using a slightly positive pressure operation to reduce nitrogen absorption during the process. 880 kg of quicklime is added in three batches. Aluminum granules and calcium carbide are used to create reducing slag, ensuring good slag fluidity. Calcium treatment is performed: 225 m of pure calcium wire is fed into the furnace during startup, followed by argon blowing for 2 minutes after the wire feeding. Soft blowing lasts 12 minutes, including 5 minutes of medium blowing followed by soft blowing to ensure inclusions are fully removed. After argon blowing, 92 kg of ladle covering agent is added per furnace. After alloying, the composition is: Si 0.038%, Mn 1.35%, B 0.0027%, Cr 0.41%, C 0.068%, and Al 0.037%. The furnace temperature at startup is 1588°C, and the outlet temperature is 1607°C.

[0036] S4, Continuous Casting: Independent casting is adopted, with protective casting throughout the process. The argon flow rate between the tundish top nozzle and the submerged entry nozzle plate is 12 NL / min, the stopper rod argon flow rate is 10 NL / min, and the top nozzle argon flow rate is 14 NL / min. Before casting, the tundish is purged with argon for 2.5 min, and a 28 m calcium line is added. During casting, the ladle must be lowered to the bottom, and the protective sleeve insertion depth is 280 mm. Low-carbon protective slag is used in the crystallizer, and carbon-free covering agent is used in the tundish. The tundish is baked for 2.7 h, and the baking temperature of the tundish and submerged entry nozzle inner wall is 1137℃, with the tundish temperature 18℃ above the liquidus temperature. The soft reduction is 2.4 mm. A constant casting speed of 1.27 m / min is maintained during the casting process. The furnace temperature at the start-up station is 1598℃.

[0037] The continuously cast billet, by weight percentage, consists of the following components: C: 0.068, Si: 0.038, Mn: 1.35, P: 0.015, S: 0.007, Al: 0.037, Cr: 0.41, Ti: 0.025, B: 0.0027, with the remainder being Fe and unavoidable impurities.

[0038] S5. Slab heating: The slab is heated in a walking beam furnace with a preheating temperature of 965°C, a heating temperature of 1160°C, and a soaking temperature of 1238°C for 3 hours to ensure that the alloying elements are fully dissolved.

[0039] S6. Hot continuous rolling: The initial rolling temperature is 1140℃ and the final rolling temperature is 850℃. The entry point of the finishing mill is descaled with high-pressure water of 22MPa, and the intervals between the stands of the finishing mill are descaled with high-pressure water of 15MPa to ensure the removal of iron oxide scale.

[0040] S7. Laminar flow cooling: After exiting the finishing mill, the strip is cooled to 660℃ by laminar flow water.

[0041] S8. Winding: After laminar flow cooling, air cool for 13 seconds to the winding temperature of 580℃.

[0042] S9. Pickling: The pickling temperature is 85℃, the pickling speed is 165m / min, the free HCl concentration in pickling tank #1 is 53g / l, and the free HCl concentration in pickling tank #3 is 160g / l.

[0043] S10, cold continuous rolling: cold rolling reduction rate is 75%;

[0044] S11, continuous annealing, galvanizing:

[0045] The preheating section heats the strip steel to 160℃ at a rate of 3℃ / s;

[0046] The heating section heats the strip steel to 825℃ at a rate of 3℃ / s.

[0047] The soaking zone holds the strip at 825℃ for 90 seconds;

[0048] The slow cooling section cools the strip steel to 700℃ at a cooling rate of 7℃ / s.

[0049] The rapid cooling section cools the strip steel to 468℃ at a cooling rate of 16℃ / s.

[0050] The equalization section activates the edge insulation function to ensure that the transverse temperature difference of the strip is less than 5℃, thereby improving the performance stability of the steel plate. The outlet temperature of the equalization section is 460℃.

[0051] The temperature of the zinc pot is 458℃, and the galvanizing time is 4 seconds;

[0052] The dew point inside the furnace is -43℃, and the oxygen content is 1ppm.

[0053] S12, Finishing: Finishing elongation rate is 0.5%.

[0054] The mechanical properties of the finished 450MPa grade galvanized duplex steel sheet prepared in Example 1 are shown in Table 1; microstructure photographs are shown below. Figure 1 As shown.

[0055] Example 2

[0056] A method for producing 450MPa grade galvanized duplex steel, the method comprising the following steps in sequence: hot metal pretreatment → converter smelting → ladle refining → continuous casting → slab heating → hot continuous rolling → laminar flow cooling → coiling → pickling → cold continuous rolling → continuous annealing and galvanizing → finishing.

[0057] S1. Hot metal pretreatment: The sulfur content of the hot metal after desulfurization is 0.007%.

[0058] S2. Converter smelting: First, 13% of the refined scrap steel by mass is added to the oxygen top and bottom blowing converter, and then 87% of the molten iron by mass is added to the oxygen top and bottom blowing converter. The final carbon content of the converter is 0.038%, the phosphorus content is 0.010%, and the tapping temperature is 1658℃. Before tapping, the ladle is pre-blown with argon for 1.8 minutes. Deoxidation and alloying begin when 1 / 5 of the steel has been tapped, and alloying is completed when 4 / 5 of the steel has been tapped. The amount of deoxidizer added is 1.87 kg / t, the amount of ferrosilicon alloy added is 2.31 kg / t, the amount of low-carbon ferromanganese added is 10.58 kg / t, the amount of ferrosilicon alloy added is 4.56 kg / t, and the amount of low-carbon ferrochrome added is 2.62 kg / t. The ladle contains 0.018% Al and 16 ppm N.

[0059] S3. Ladle Refining: The molten steel is refined using a slightly positive pressure operation to reduce nitrogen absorption during the process. 920 kg of quicklime is added in three batches. Aluminum granules and calcium carbide are used to create reducing slag, ensuring good slag fluidity. Calcium treatment is performed, with 193 m of pure calcium wire fed per continuous casting, followed by 2 minutes of argon blowing. Soft blowing lasts 13 minutes, including 5 minutes of medium blowing followed by soft blowing to ensure inclusions are fully removed. After argon blowing, 115 kg of ladle covering agent is added per furnace. After alloying, the composition is: Si 0.041%, Mn 1.39%, B 0.0033%, Cr 0.42%, C 0.066%, and Al 0.047%. The arrival temperature at the station for the continuous casting is 1559℃, and the exit temperature is 1581℃.

[0060] S4. Continuous Casting: Independent casting is adopted, with protective casting throughout the process. The argon flow rate between the tundish top nozzle and the submerged entry nozzle plate is 13 NL / min, the stopper rod argon flow rate is 9 NL / min, and the top nozzle argon flow rate is 15 NL / min. Before casting, the tundish is purged with argon for 2 minutes, and a 22m calcium line is added. During casting, the ladle must be lowered to the bottom, and the protective sleeve is inserted to a depth of 270mm. Low-carbon protective slag is used in the crystallizer, and carbon-free covering agent is used in the tundish. The tundish is baked for 3 hours, and the baking temperature of the tundish and submerged entry nozzle inner wall is 1146℃, with the tundish temperature 19℃ above the liquidus temperature. The soft reduction is 2.3mm. A constant casting speed is maintained during the casting process, with a casting speed of 1.26m / min. The temperature of the continuous casting furnace is 1577℃ upon arrival at the station.

[0061] The continuously cast billet, by weight percentage, consists of the following components: C: 0.066, Si: 0.041, Mn: 1.39, P: 0.011, S: 0.005, Al: 0.047, Cr: 0.42, Ti: 0.029, B: 0.0033, with the remainder being Fe and unavoidable impurities.

[0062] S5. Slab heating: The slab is heated in a walking beam furnace with a preheating temperature of 960°C, a heating temperature of 1165°C, and a soaking temperature of 1240°C for 2.8 hours to ensure that the alloying elements are fully dissolved.

[0063] S6. Hot continuous rolling: The initial rolling temperature is 1144℃ and the final rolling temperature is 858℃. The entry point of the finishing mill is descaled with high-pressure water at 23MPa, and the intervals between the stands of the finishing mill are descaled with high-pressure water at 14MPa to ensure the removal of iron oxide scale.

[0064] S7. Laminar flow cooling: After exiting the finishing mill, the strip is cooled to 665℃ by laminar flow water.

[0065] S8. Winding: After laminar flow cooling, air cool for 13 seconds to the winding temperature of 565℃.

[0066] S9. Pickling: The pickling temperature is 88℃, the pickling speed is 170m / min, the free HCl concentration in pickling tank #1 is 48g / l, and the free HCl concentration in pickling tank #3 is 156g / l.

[0067] S10, cold continuous rolling: cold rolling reduction rate is 77%;

[0068] S11, continuous annealing, galvanizing:

[0069] The preheating section heats the strip steel to 160℃ at a rate of 5℃ / s;

[0070] The heating section heats the strip steel to 835℃ at a rate of 4℃ / s.

[0071] The soaking zone holds the strip at 835℃ for 85 seconds.

[0072] The slow cooling section cools the strip steel to 680℃ at a cooling rate of 9℃ / s.

[0073] The rapid cooling section cools the strip steel to 464℃ at a rate of 15℃ / s.

[0074] The equalization section activates the edge insulation function to ensure that the transverse temperature difference of the strip is less than 5℃, thereby improving the performance stability of the steel plate. The outlet temperature of the equalization section is 460℃.

[0075] The temperature of the zinc pot is 459℃, and the galvanizing time is 3 seconds;

[0076] The dew point inside the furnace is -44℃, and the oxygen content is 1ppm.

[0077] S12, Finishing: Finishing elongation rate is 0.5%.

[0078] The mechanical property test results of the 450MPa grade galvanized duplex steel sheet prepared in Example 2 are shown in Table 1; microstructure photographs are shown below. Figure 2As shown.

[0079] Table 1. Mechanical property test results of the finished steel plates prepared in the examples.

[0080] Example 1 285 466 32.5 0.19 53 Example 2 289 483 34.0 0.18 60

[0081] This invention adds an appropriate amount of Cr to ensure hardenability, without adding the more expensive Mo element, thus achieving tensile strength that meets standard requirements. The continuous annealing process maintains low dew point and oxygen content control. Good coating quality is achieved through low Si composition design, good billet surface quality, and hot-rolled plate quality. Precise control of chemical composition design and converter smelting and ladle refining effectively reduces nitrogen and inclusion content in the steel, improving its castability. Strict control of pouring temperature, casting speed, and soft reduction during continuous casting ensures good billet surface and internal quality. The appropriate addition of fine-graining element Ti, combined with low-temperature coiling and high cold rolling reduction, facilitates better microstructure and mechanical properties after continuous annealing and galvanizing. The finer grain structure after continuous annealing, combined with finishing, effectively regulates yield strength, meeting requirements for yield strength ratio, stamping performance, and flange flanging performance.

[0082] For anyone skilled in the art, many possible variations and modifications can be made to the technical solutions of this invention, or equivalent embodiments can be modified based on the disclosed technical content, without departing from the scope of the technical solutions of this invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of this invention without departing from the content of the technical solutions of this invention should still fall within the protection scope of the technical solutions of this invention.

Claims

1. A 450MPa grade galvanized duplex steel, characterized in that, The galvanized duplex steel, by weight percentage, consists of the following components, C: 0.04~0.08, Si: 0.020~0.060, Mn: 1.30~1.60, P≤0.020, S≤0.010, Al: 0.015~0.055, Cr: 0.30~0.50, Ti: 0.015~0.040, B: 0.0020~0.0040, with the remainder being Fe and unavoidable impurities; The production method of the 450MPa grade galvanized duplex steel includes the following steps: hot metal pretreatment → converter smelting → ladle refining → continuous casting → slab heating → hot continuous rolling → laminar flow cooling → coiling → pickling → cold continuous rolling → continuous annealing and galvanizing → finishing. The molten iron pretreatment includes desulfurization of the molten iron to S≤0.010%; Converter smelting: Control the final C content at the converter endpoint to be ≤0.04%, P to ≤0.015%, and the tapping temperature to ≥1650℃; pre-purge the ladle with argon for 1~2 minutes before tapping; begin deoxidation and alloying when 1 / 5 of the steel has been tapped, and complete the alloying when 4 / 5 of the steel has been tapped. The amounts of deoxidizer added are 1.5~2.0 kg / t, ferrosilicon alloy added are 2.2~2.4 kg / t, low-carbon ferromanganese added are 10~11 kg / t, ferrosilicon-manganese alloy added are 4~5 kg / t, and low-carbon ferrochrome added are 2~3 kg / t; control the Al content in the ladle to be 0.005~0.020%, and N to ≤25 ppm; Ladle refining: 800-1000 kg of quicklime is added in 2-3 batches; aluminum granules and calcium carbide are used to create reducing slag; calcium treatment: 200-250 m of pure calcium wire is fed into the furnace during start-up, and 180-200 m of pure calcium wire is fed into the furnace during continuous casting. After feeding the calcium wire, argon blowing continues for 1-2 minutes; soft blowing time is ≥10 minutes, including 5 minutes of medium blowing followed by soft blowing to ensure that inclusions are fully floated and removed; after argon blowing, the amount of covering agent added to the ladle is 80-120 kg / furnace; alloying requirements: Si, Mn, B and Cr are controlled at the median value, C is controlled at 0.060-0.070%, and Al is controlled at 0.025-0.050%; the temperature at the furnace during start-up is 1580±10℃, and the temperature at the furnace exit is 1600±10℃; the temperature at the furnace during continuous casting is 1555±10℃, and the temperature at the furnace exit is 1575±10℃. The slab heating process involves heating the slab in a walking beam furnace with a preheating temperature of 950±20℃, a heating temperature of 1150±20℃, a soaking temperature of 1230±20℃, and a heating time of 2.5±0.5 h. The hot continuous rolling mill has an initial rolling temperature of 1130±20℃ and a final rolling temperature of 870±20℃. The finishing mill inlet is descaled with high-pressure water of ≥20MPa, and the finishing mill stands are descaled with high-pressure water of ≥10MPa. The continuous annealing and galvanizing process is as follows: The preheating section heats the strip to 150-180℃ at a rate of 2-6℃ / s; the heating section heats the strip to 820-850℃ at a rate of 2-4℃ / s; the soaking section holds the strip at 820-850℃ for 50-110 seconds; the slow cooling section cools the strip to 680-750℃ at a rate of 5-10℃ / s; the rapid cooling section cools the strip to 450-480℃ at a rate of 10-20℃ / s; the equalization section activates edge insulation to ensure a transverse temperature difference of less than 5℃, and the equalization section outlet temperature is 450-470℃; the zinc pot temperature is 455-460℃, and the galvanizing time is 2-5 seconds; the furnace dew point is ≤-40℃, and the oxygen content is ≤2ppm. The winding process involves laminar flow cooling followed by air cooling for 10-20 seconds to a winding temperature of 550-600℃.

2. The 450MPa grade galvanized duplex steel according to claim 1, characterized in that, The continuous casting adopts independent casting cycles with full-process protective casting. The argon flow rate between the tundish top nozzle and the submerged entry nozzle plate is 10~14 NL / min, the argon flow rate of the stopper rod is 8~10 NL / min, and the argon flow rate of the top nozzle is 14~16 NL / min. Before casting, the tundish is purged with argon for 2~3 min, and a calcium addition line of 20~40m is added. During casting, the ladle is dropped to the bottom, and the protective sleeve is inserted to a depth ≥200 mm. Low-carbon protective slag is used in the crystallizer, and low-carbon or carbon-free covering agent is used in the tundish. The tundish is baked for ≥2.5h, and the baking temperature of the inner wall of the tundish and submerged entry nozzle is ≥1100℃. The tundish temperature is controlled at 10~25℃ above the liquidus temperature. The soft reduction is 2.2~2.6 mm. The casting speed range during the steel casting process is 1.20~1.30 m / min. The temperature of the furnace arriving at the station for the start-up furnace is 1595±10℃, and the temperature of the furnace arriving at the station for the continuous casting furnace is 1570±10℃.

3. The 450MPa grade galvanized duplex steel according to claim 1, characterized in that, The laminar flow cooling: After exiting the finishing mill, the strip is cooled to 650~700℃ by laminar water cooling.

4. The 450MPa grade galvanized duplex steel according to claim 1, characterized in that, The pickling process is as follows: the pickling temperature is 70~90℃, the pickling speed is 60~180 m / min, the free HCl concentration in pickling tank #1 is ≥40 g / l, and the free HCl concentration in pickling tank #3 is ≥140 g / l.

5. The 450MPa grade galvanized duplex steel according to claim 1, characterized in that, The cold rolling continuous rolling process has a cold rolling reduction rate of ≥70%.

6. The 450MPa grade galvanized duplex steel according to claim 1, characterized in that, The finishing process has an elongation rate of 0.4-0.8%.

Citation Information

Patent Citations

  • High-strength cold-rolled hot-galvanized dual-phase steel plate and manufacture method thereof

    CN102719751A

  • Cold-rolled hot-galvanized dual-phase steel and preparation method thereof

    CN103938097A

  • 450MPa grade hot-dip galvanized duplex steel and its production method

    CN113584395B

  • 450MPa-grade hot-dip galvanized dual-phase steel with high work hardening rate and surface quality and production method of 450MPa-grade hot-dip galvanized dual-phase steel

    CN114107806A

  • Production method of cold-rolled dual phase steel with tensile strength of 450MPa

    CN102732791A